-1/9(y-3)=1/6(y+6)

Simple and best practice solution for -1/9(y-3)=1/6(y+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/9(y-3)=1/6(y+6) equation:



-1/9(y-3)=1/6(y+6)
We move all terms to the left:
-1/9(y-3)-(1/6(y+6))=0
Domain of the equation: 9(y-3)!=0
y∈R
Domain of the equation: 6(y+6))!=0
y∈R
We calculate fractions
(-6yy/(9(y-3)*6(y+6)))+(-9yy/(9(y-3)*6(y+6)))=0
We calculate terms in parentheses: +(-6yy/(9(y-3)*6(y+6))), so:
-6yy/(9(y-3)*6(y+6))
We multiply all the terms by the denominator
-6yy
Back to the equation:
+(-6yy)
We calculate terms in parentheses: +(-9yy/(9(y-3)*6(y+6))), so:
-9yy/(9(y-3)*6(y+6))
We multiply all the terms by the denominator
-9yy
Back to the equation:
+(-9yy)
We get rid of parentheses
-6yy-9yy=0

See similar equations:

| 3x+20=+4x-1 | | p^2+5p=84=0 | | 77=7(m+3.7) | | -33/1=1/2g | | 2÷3y-1÷6y+4=19 | | 4w=6w+11 | | 12(2.5)=2x2-3x+7 | | 12(2.5)=2x2−3x+7 | | (3x+8)=(7x+4) | | -2-(3+x)=5 | | 3y-1=2y | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x+12 | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x+6 | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x+ | | 2576=23(p+35) | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x-6 | | (3x+29)+(6x+7)=180 | | 12c^2-36c=0 | | 2576=23(p+23) | | 4a+12a=0 | | 15-10y=4y-16 | | -5(1-w)=10 | | 7m-12=30 | | 2-4n=7n+3. | | 3x+11x/3=100 | | 6+4m=-10 | | 4x2−4x−3=0 | | 0.5y-y=-9 | | 1/3a+1/2=10 | | 15/x+2=5 | | 4(x+3)-10=10 | | n^+6n+5=8 |

Equations solver categories